Zambia : Fourth Review of the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Modification of Performance Criteria, and Financing Assurances Review; Staff Report; and Press Release on the Executive Board Consideration. (IMF Staff Country Reports; Country Report ;, 2006)
Zambia has achieved robust economic growth over the years, and poverty has begun to trend downward under the Poverty Reduction and Growth Facility Arrangement. Prudent fiscal policy has reduced the domestic financing need and facilitated the implementation of a firmer monetary policy. Executive Directors agreed that the relief under the economic program and the Multilateral Debt Relief Initiative has reduced its external debt, and its economic fundamentals have helped in gaining market confidence. They advised the authorities to maintain macroeconomic stabilization and stressed the need to accelerate structural reform.